The classification of muscle injuries: a critical review - Bisciotti, G. N.; Balzarini, L.; Volpi, P. (Medicina dello Sport, 2015)
The study of the classification of muscle injuries is going through a period of great scientific interest, the incontrovertible testimony is represented by the great numbers of studies available in literature. However, some basic aspects of the problem as, in our view, the objective staging of the extension of the lesion, its proximity to the tendon structures and some specific nosological framework , as the fascial lesions, have yet to be fully clarified, particularly in relationship of their strong prognostic value. In this paper, after a brief historical overview of the study of classifications of muscle injuries, we will discuss some specific issues that, in our opinion, require special consideration.